Transcriptional Repression of pref-1 by Glucocorticoids Promotes 3T3-L1 Adipocyte Differentiation - Smas, C M; Chen, L; Zhao, L; Latasa, M J; Sul, H S (The Journal of biological chemistry, 1999)
Pref-1 is an epidermal growth factor-like domain-containing transmembrane protein that is cleaved to generate a soluble factor. It is abundant in 3T3-L1 preadipocytes but absent in mature adipocytes. Constitutive expression of pref-1 or the addition of its ectodomain inhibits adipogenesis. We find that the pref-1 gene is an early target of dexamethasone, a component of the dexamethasone/methylisobutylxanthine differentiation mixture used routinely for adipoconversion. The time course of the decrease in pref-1 mRNA by dexamethasone reflected the pref-1 mRNA half-life determined by actinomycin D treatment. Nuclear run-on assays showed that dexamethasone attenuates pref-1 transcription. We demonstrate a correlation between pref-1 down-regulation and adipoconversion by varying the time period and concentration of dexamethasone. Increasing the dexamethasone treatment from 2 to 4 days resulted in a time-dependent pref-1 down-regulation and increased differentiation as measured by adipocyte marker mRNAs. The dexamethasone concentration between 1 and 10 n m showed a dose-dependent decrease in pref-1 mRNA and an enhancement of adipogenesis. To test the hypothesis that dexamethasone initiation of adipoconversion may be via down-regulation of pref-1 , we lowered endogenous pref-1 mRNA levels by stably transfecting 3T3-L1 preadipocytes with antisense pref-1. At 1 Î¼ m , antisense cells had enhanced adipose conversion; a similar degree of differentiation occurred with 2 n m dexamethasone, a concentration that does not support differentiation of control 3T3-L1 cells. We conclude that dexamethasone-mediated repression of pref-1 contributes to the mechanisms whereby glucocorticoids promote adipogenesis.